Artificial Intelligence in Brazilian Law Courts: risks and governance standards - Santos, Taina T. C. dos; Wassermann, Renata; Maranhao, Juliano (Anais da Conferência Latino-Americana de Ética em Inteligência Artificial (LAAI-Ethics), 2024)
This paper examines the present application of Artificial Intelligence (AI) systems in Brazilian law courts, focusing on potential risks and ethical concerns associated with its integration. While AI has the potential to enhance productivity, its application in sensitive domains like criminal justice demands rigorous Verification and Validation (V&V) processes to mitigate biased outcomes. The study argues for classifying AI tools used in law enforcement as high-integrity systems and advocates adherence to standards such as IEEE 1012-2016. It underscores the need for comprehensive regulation and specialized training to address issues related to bias and privacy breaches, ensuring the responsible deployment of AI systems in the activities of law courts.